Teaching of the Production and Acceptance Analysis of Instant Urap Seasoning in the Vocational School - Rahmadhani, Reno; Sitiawati, Tati; Mahmudatussa’ada, Ai; Mupita, Jonah (Indonesian Journal of Multidiciplinary Research, 2021)
Urap is one of the salads or side dishes of Indonesian vegetables originating from the island of Java with the basic ingredients of half-old grated coconut and seasoned then mixed with vegetables with a spicy, savory, and fresh taste. In general, the urap seasoning does not last long after being mixed with vegetables. It will quickly go stale. Instant urap seasoning is a solution to go stale quickly, besides being durable, it can be used practically. The purpose of this study was to teach how to make instant urap seasoning and determine the public's acceptance. The method is the experimental method, involving 35 people consisting of 4 expert panelists, 9 trained panelists, and 22 untrained panelists. The instruments were hedonic test sheets and organoleptic test sheets. The results showed that The addition of coriander and lime juice affected the taste and aroma of the family recipe instant ointment. Thus, it made the aroma and taste of the family recipe instant ointment more fragrant and savory. The difference in the addition of palm sugar also affects the color difference between the two instant urap spices. The effect of the comparison of chili types has an impact on the flavors. The family recipe instant urap seasoning product is well received by the public.